Tumpang Tindih Kewenangan Bawaslu, DKPP Dan PTUN Dalam Sengketa Pilkada Dan Implikasinya Terhadap Hukum - Suciara, Angelica; Idias, Bryan; Siregar, Nathasya Jhonray; Siregar, Tasya Amira Frananda; Prabowo, Tri Widyasto (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This article discusses the disharmony of authority among The General Election Supervisory Agency (Bawaslu), the Election Organizer Ethics Council (DKPP), and the Administrative Court (PTUN) in resolving regional election (Pilkada) disputes, particularly administrative disputes. The study aims to analyze the potential overlaps in jurisdiction among these institutions and their impact on legal certainty and the protection of constitutional rights of Pilkada participants. This research employs a normative legal approach supported by case studies of Pilkada dispute decisions handled simultaneously by the three institutions. The findings reveal that the absence of clear procedural boundaries leads to systemic confusion, undermines institutional effectiveness, and harms citizens' rights. This research employs a normative legal approach supported by case studies of Pilkada dispute decisions handled simultaneously by the three institutions. The findings reveal that the absence of clear procedural boundaries leads to systemic confusion, undermines institutional effectiveness, and harms citizens' rights.